Agriculture in Nicaragua : Performance, Challenges, and Options - Piccioni, Norman Bentley (World Bank, Washington, DC, 2017)
This work summarizes background papers prepared for the World Bank Group with significant input from government counterparts and other development partners. It takes stock of major recent developments and argues that a lot has been achieved in the last decade in terms of production of commodities for export and food consumption, with favorable impact on rural poverty reduction. It also argues that the two factors driving the recent agricultural performance, namely favorable international prices and expansion of the agricultural frontier, have reached their limits. So while trade policies are broadly on target, much can be done by focusing on the productivity of small family agriculture and improving competitiveness by reducing transaction costs (logistics) affecting small, medium, and large commercial farms. In the short to medium term, the household income of the rural poor will continue to depend largely on agriculture. Thus interventions will need to take into account the heterogeneity of smallholder agriculture while simultaneously increasing its resilience to climate risks through climate-smart agriculture.